Building Information Modeling-Based Building Energy Modeling: Investigation of Interoperability and Simulation Results - Elnabawi, Mohamed H. (Frontiers in Built Environment, 2020)
There is increasing need to apply Building Information Modelling (BIM) to low energy buildings, and this includes building energy modelling (BEM). If a building energy model can be flawlessly generated from a BIM model, the energy simulation process can be integrated better within the design, more competent, and timesaving. However, concerns about both the reliability and integrity of the data transfer process and the interoperability between the BIM and BEM prevent any implementation of BIM-based energy modelling on a large scale. This study addresses the accuracy and integrity of BIM-based energy modelling by comparing how well AutoDesk, REVIT (BIM), and DesignBuilder (BEM) identified areas of interoperability, including: location and weather files, geometry, construction and materials, thermal zones, occupancy operating schedules, and HVAC systems. All misrepresented data during the interoperability process were identified, and the BIM-based energy modelling simulation outcomes were compared to the actual energy consumption of the case study, to assess the reliability of the process, and good overall conformity was found. The investigation has revealed a number of interoperability issues regarding the BIM data input and BEM data interpretation. Overall, BIM-based energy modelling proved to be a reliable tool for sustainable and low energy building design, but the BIM to BEM process is a non-standardised method of producing building energy models as it varies from one modeller to another.